Circular RNA signature of aggressive CLL with t(14;19)(q32;q13). An ERIC study - Eleonora Roncaglia; Enrico Gaffo; Giulia Calabretto; Moritz Fürstenau; Kerry A. Rogers; Panagiotis Baliakas; Chenghua Cui; Cecelia Miller; Claudia Haferlach; Karla Plevova; David Oscier; Zadie Davis; et al. (Journal of Hematology & Oncology)
Abstract In Chronic Lymphocytic Leukemia (CLL), t(14;19)(q32;q13), leading to the overexpression of BCL3, is found in ∼1% of cases and is associated with an aggressive disease. In this study, leveraging a large CLL patient cohort collected thanks to an international collaboration, we investigate for the first time the circular transcriptome (circRNAome) associated with the rare t(14;19), in comparison with CLL without t(14;19) and B cells of age-matched healthy donors. We described the circRNAs commonly dysregulated in CLL, including circCSNK1G3 and circEXOC6B(3–5), which were depleted, and circZNF609 and circLPAR3, which were overexpressed in malignant cells. Of importance, we disclosed the circRNA signature of CLL with t(14;19), formed by circRNAs with expression significantly altered specifically in link with this lesion, ectopically expressed like circCDK14(3–4), circCORO1C, circCLEC2D, and circEMB, or downregulated like circCEP70(3–6). Several of these molecules were previously shown to be dysregulated or play a role in cancer, whereas most of the signature circRNAs deserve further investigation. CLL patients with high circCORO1C and circCLEC2D expression had significantly worse clinical outcomes, with shorter time to first treatment and overall survival. This study disclosed new molecular features of the aggressive CLL subtype with t(14;19).